The effects of steel X-brace retrofitting of RC frames on the seismic performance of frames and their elements. (1st March 2020) - Rahimi, A; Maheri, Mahmoud R.
Highlights: Global performance of RC frames retrofitted by X braces are investigated. Nonlinear time history analyses are used to study the effects of retrofitting. X bracing reduces maximum displacement, inter-storey drifts and demand base shear. Effectiveness of bracing system is reduced as the height of frame increases. Retrofitting reduces ductility and shear demands in beams and joints in low-rise frames. Abstract: Steel X braces are used extensively to retrofit RC frames. When steel braces are added to an existing RC frame, the load paths through which the lateral forces are transferred change considerably, resulting in changes in demand on the frame and its elements. The present study attempts to examine the possible side effects of retrofitting RC frames with steel X braces, regarding their overall seismic performance such as global displacements, drifts and base shears, as well as, their individual members, including beams and joints. To this end, a large number of nonlinear time history seismic analyses are performed on retrofitted 2D, RC frames, being 4, 8 and 12 storeys high. It is found that, retrofitting an RC frame with steel X braces improves its global seismic response by reducing the maximum displacement, inter-storey drifts and demand base shear. However, the effectiveness of the bracing system in improving global responses is generally reduced as the height of the frame increases. Regarding the local effects on beams and joints, it is noted that although retrofitting, in general, reduces ductility demand in beams, and shear demand in joints, the reductions are not substantial in taller frames and in some beams and joints retrofitting may even have an adverse effect. Also, the connections between the steel X brace system and the RC frame cause the plastic hinges in beams and columns to relocate further away from the joint, resulting in a reduction in the effective length and possible increase in the level of plastic shear in these members. The local adverse effects of retrofitting an RC frame by steel X-braces may necessitate prior local strengthening of some members.